2022
DOI: 10.3390/cancers14102565
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate Plus Buformin in AML: A Metabolic Targeted Treatment

Abstract: In the present study, we characterized the metabolic background of different Acute Myeloid Leukemias’ (AMLs) cells and described a heterogeneous and highly flexible energetic metabolism. Using the Seahorse XF Agilent, we compared the metabolism of normal hematopoietic progenitors with that of primary AML blasts and five different AML cell lines. We assessed the efficacy and mechanism of action of the association of high doses of ascorbate, a powerful oxidant, with the metabolic inhibitor buformin, which inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…They were used, among others, to determine the effect of ascorbate and buformin on the metabolic activity of AML cells. Studies confirmed the clinical assessment of the efficacy of the combination of these compounds in treating refractory cases of AML [ 99 ]. Bioenergetic analysis on OCI-AML2 and OCI-AML3 lines showed that AMPK / PERK activation by GSK621 induces mitochondrial apoptosis in leukemic cells [ 100 ].…”
Section: Aml Cell Lines and Typesmentioning
confidence: 76%
“…They were used, among others, to determine the effect of ascorbate and buformin on the metabolic activity of AML cells. Studies confirmed the clinical assessment of the efficacy of the combination of these compounds in treating refractory cases of AML [ 99 ]. Bioenergetic analysis on OCI-AML2 and OCI-AML3 lines showed that AMPK / PERK activation by GSK621 induces mitochondrial apoptosis in leukemic cells [ 100 ].…”
Section: Aml Cell Lines and Typesmentioning
confidence: 76%
“…Moreover, ascorbate also shows the ability to induce cell death by targeting glycolytic metabolism in primary AML blasts, through the inhibition of hexokinase 1/2 (HK1/2) and GLUT1 in hematopoietic cells, and, in combination with the metabolic inhibitor buformin, also decreases mitochondrial respiration and ATP production, sparing healthy CD34 + cells. Overall, these data clearly depict an effect of ascorbate on glycolysis and contribute to elucidate the targets and mechanisms through which this therapeutic agent exerts its anti-cancer effects (Banella et al, 2022).…”
Section: Targeting Aml Driver Mutations Using Ascorbic Acid: From In ...mentioning
confidence: 80%
“…The goal of this study was to evaluate if triheptanoin can ameliorate the glycolytic and oxidative metabolism when administered to fibroblasts of patients with NLSD-M. The method used to analyze the oxidative metabolism of affected fibroblasts has been widely used in other studies, mainly for oncological pathologies [ 7 , 8 , 10 ], but has never been used for the study of NLSD. The results demonstrate that triheptanoin ameliorates the metabolic performances in NLSD-M fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, cells use the spare respiratory capacity (SRC). This process is tightly controlled by the nature and flow of nutrients that can be oxidized in the mitochondrial matrix by the tricarboxylic acid (TCA) cycle [ 8 ]. SRC is increased in all NLSD-M patients after treatment with triheptanoin, indicating that acetyl-CoA and Propionyl-CoA, the metabolized products of triheptanoin, provide an anaplerotic effect by replenishing deficient TCA cycle intermediates in NLSD-M. SRC represents a particularly robust functional parameter to evaluate mitochondrial reserve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation